2000
DOI: 10.1097/00000539-200006000-00028
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tramadol and Morphine on Immune Responses and Pain After Surgery in Cancer Patients

Abstract: Recent studies suggest that opioids can have an adverse impact on the immune system. Because surgical stress also induces immune dysfunction, the search for analgesic drugs devoid of immunosuppressive effects is of import. This study compared the effects on immune responses of morphine and of the atypical opioid analgesic, tramadol, given for postoperative pain to gynecological cancer patients. Tramadol and morphine showed comparable analgesic activity; however, tramadol, in contrast to morphine, induced an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
196
3
23

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(230 citation statements)
references
References 24 publications
8
196
3
23
Order By: Relevance
“…8 Opioid analgesics inhibit both cellular and humoral immune function in humans. 9,10 Furthermore, morphine is pro-angiogenic and promotes breast tumour growth in rodents. 11 Consistent with this theory, surgical studies in animals indicate that regional anesthesia and optimum postoperative analgesia independently reduce the metastatic burden in animals inoculated with breast adenocarcinoma cells.…”
Section: Résumémentioning
confidence: 99%
“…8 Opioid analgesics inhibit both cellular and humoral immune function in humans. 9,10 Furthermore, morphine is pro-angiogenic and promotes breast tumour growth in rodents. 11 Consistent with this theory, surgical studies in animals indicate that regional anesthesia and optimum postoperative analgesia independently reduce the metastatic burden in animals inoculated with breast adenocarcinoma cells.…”
Section: Résumémentioning
confidence: 99%
“…It has been shown previously that the magnitude of such stress response is proportional to the magnitude of injury, [1][2][3][4] to the total operating time 5,6 as well as to the amount of intraoperative blood loss 7,8 and to the degree of postoperative pain; 9,10 furthermore, it has been shown that the choice of anesthetic technique may modulate the extent of such response. [11][12][13][14][15] Decreasing the stress response to surgery and trauma is of high relevance to the anesthesiologist, since it may allow complex operations in high risk patients [American Society of Anesthesiologist (ASA) III-IV, malnourished, immunocompromised and/or elderly)]; [16][17][18] it has been suggested that decreasing operative stress may be a key factor in improving outcome and lowering the length of hospital stay as well as the total costs of patients care. 6,19,20 Thus, an important goal of current research on new anesthetics is to find the ideal "stress free" anesthetic, to limit the activation of the neuroendocrine, inflammatory and immune responses.…”
Section: Me Et Th Ho Od D:mentioning
confidence: 99%
“…10,11 Thirdly, opioid analgesics such as morphine and fentanyl, which are given to control surgical pain, might inhibit both cellular and humoral immune function in humans. 10,12 Fourthly, pain per se enhances the tumourpromoting effects of surgery and suppresses cell-mediated immunity. 4 Fortunately, previous investigations have demonstrated that regional anaesthesia, including epidural anaesthesia and spinal block, can attenuate or prevent these adverse effects.…”
Section: Introductionmentioning
confidence: 99%